Combined therapy of bilateral transcranial direct current stimulation and ocular occlusion improves visual function in adults with amblyopia, a randomized pilot study - Castillo-Astorga, Raul; Del Valle-Batalla, Lucia; Mariman, Juan José; Plaza-Rosales, Ivan; de los Angeles Juricic, Maria; Maldonado, Pedro Esteban; Vogel, Marlene; Fuentes-Flores, Romulo (Frontiers in Human Neuroscience, 2023)
Background: Amblyopia is the interocular visual acuity difference of two lines or more with the best correction in both eyes. It is treated with ocular occlusion therapy, but its success depends on neuroplasticity, and thus is effective in children but not adults. Transcranial Direct Current Stimulation (tDCS) is suggested to increase neuroplasticity. Objective: To determine if combined intervention of bilateral tDCS and ocular occlusion improves visual function in adults with amblyopia. Methods: A double-blind randomized, controlled pilot trial was conducted in 10 volunteers with amblyopia. While applying ocular occlusion and performing a reading task, participants received bilateral tDCS (n=5) or sham stimulation (n=5), with the anodal tDCS electrode in the contralateral visual cortex and the cathodal in the ipsilateral visual cortex in relation to the amblyopic eye. Visual function (through visual acuity, stereopsis, and contrast sensitivity tests) and visual evoked potential (with checkerboard pattern stimuli presentation) were evaluated immediately after. Results: Thirty minutes after treatment with bilateral tDCS, visual acuity improved by 0.16 (+/- 0.025) LogMAR in the treatment group compared with no improvement (-0.02 +/- 0.02) in 5 controls (p=0.0079), along with a significant increase in the amplitude of visual evoked potentials of the amblyopic eye response (p=0.0286). No significant changes were observed in stereopsis and contrast sensitivity. No volunteer reported any harm derived from the intervention. Conclusions: Our study is the first to combine anodal and cathodal tDCS for the treatment of amblyopia, showing transient improved visual acuity in amblyopic adults.